Three Models of Firm Behavior; Theory and Estimation, with an Application to the Dutch Manufacturing Sector - van der Loeff, S. Schim; Harkema, R. (The Review of Economics and Statistics, 1976)
S. Schim van der Loeff, R. Harkema, Three Models of Firm Behavior; Theory and Estimation, with an Application to the Dutch Manufacturing Sector, The Review of Economics and Statistics, Vol. 58, No. 1 (Feb., 1976), pp. 13-21